Influence of Harvesting Time on the Chemical Composition of Wild Stinging Nettle (Urtica dioica L.) - Aurelija Paulauskienė; Živilė Tarasevičienė; Valdas Laukagalis (Plants, 2021)
This research aimed to determine the effect of different harvesting times on the chemical composition of stinging nettle (Urtica dioica L.). The leaves of nettle were harvested at the same place once a month in the period of April–September 2019. The analysis focused on the contents of dry matter, soluble solids, ascorbic acid, titratable acidity, chlorophyll a and chlorophyll b, total carotenoids, total phenolic compounds, antioxidant activity, ash content, and macro- and microelements. The nettles harvested in April were characterized by the highest levels of soluble solids and some macro-and microelements (P, K, Fe, Zn). The plants harvested in May were distinguished for titratable acidity, chlorophyll a, chlorophyll b, and carotenoid contents. In this month, the plants were determined to have the highest antioxidant activity during the entire vegetation period. The plants collected in July contained the highest amount of Mn, but the antioxidant activity of these plants was the lowest during the vegetation period. In August, the plants had the highest levels of ascorbic acid, phenolic compounds, and ash, while the plants collected in September were characterized by having the highest amounts of Ca, Mg, and B as compared to those established in other months of vegetation.